Cadmium disrupts autophagic flux by inhibiting cytosolic Ca2+-dependent autophagosome-lysosome fusion in primary rat proximal tubular cells. (15th May 2017) - Liu, Fei; Wang, Xin-Yu; Zhou, Xu-Ping; Liu, Zong-Ping; Song, Xiang-Bin; Wang, Zhen-Yong; Wang, Lin
Abstract: Previous studies have shown that subcellular Ca 2+ redistribution is involved in Cd-induced autophagy inhibition in primary rat proximal tubular (rPT) cells, but the mechanism remains unclear. In this study, the status of autophagic flux was monitored by the GFP and RFP tandemly tagged LC3 method. Pharmacological inhibition of cytosolic Ca 2+ concentration ([Ca 2+ ]c ) with 2-APB or BAPTA-AM significantly alleviated Cd-elevated yellow puncta formation and restored Cd-inhibited red puncta formation, while thapsigargin (TG) had the opposite regulatory effect, demonstrating that Cd-induced [Ca 2+ ]c elevation inhibited the autophagic flux in rPT cells. Resultantly, Cd-induced autophagosomes accumulation was obviously modulated by 2-APB, BAPTA-AM and TG, respectively. Meanwhile, blockage of autophagosome-lysosome fusion and decreased recruitment of Rab7 to autophagosomes by Cd exposure was noticeably restored by 2-APB or BAPTA-AM, but co-treatment with Cd and TG further impaired Cd-induced autophagy arrest. Moreover, Cd-induced oxidative stress intimately correlated with cytosolic Ca 2+ mobilization, and N-acetylcysteine (NAC) markedly rescued Cd-blocked autophagosome-lysosome fusion and recruitment of Rab7 to autophagosomes in rPT cells, implying that Cd-induced autophagy inhibition was due to [Ca 2+ ]c elevation-triggered oxidative stress. In summary, these results suggest that Cd-mediated autophagy inhibition in rPT cells is dependent on cytosolic Ca 2+ overload. Elevation of [Ca 2+ ]c inhibited the autophagosome-lysosome fusion to block the degradation of autophagosomes, which aggravated Cd-induced cytotoxicity in rPT cells.